Chain-locked precursor ion scanning based HPLC–MS/MS for in-depth molecular analysis of lipase-catalyzed transesterification of structured phospholipids containing ω-3 fatty acyl chains. (15th January 2023) - Zhang, Min; Wang, Pingya; Jin, Danping; Jian, Shikai; Wu, Jiahui; Huang, Min; Xie, Hujun; Zhao, Qiaoling; Yang, Huicheng; Luo, Pei; Yuan, Hong; Xue, Jing; et al.
Graphical abstract: Highlights: Conditions of lipase-catalyzed transesterification were optimized. Precursor ion scan was employed to identify and quantify the intact phospholipid. Product ions of m / z 301.6 for EPA and m / z 327.6 for DHA were locked. PLS-DA model and HCA were applied for comparing lipidomics profiles. Abstract: Lipase-catalyzed transesterification of structured phospholipids (sPLs) is a hot topic, but the structural variation of the fatty acyl chains in intact phospholipids at the molecular level remains unclear to date. The present study explored the detailed characteristics of synthesized phospholipids through high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) in precursor ion scan mode. The optimal conditions were in-depth inspected and determined for the reaction system, including phospholipase A1 as catalyst, 15% lipase loading, and 1% water content. The sPLs enriched with EPA/DHA were structurally and quantitatively characterized by focusing on the fragments of m / z 301.6 (eicosapentaenoic acid, EPA) and m / z 327.6 (docosahexaenoic acid, DHA), and the results were statistically analyzed using partial least squares discriminant analysis and clustered heatmap hierarchical clustering analysis. PC 38:6 (18:1/20:5), PC 38:7 (18:2/20:5), PC o-40:6 (o-18:0/22:6), and PE 40:8 (18:2/22:6) etc. were revealed as the main variables that were active in the reaction.